Pengembangan Usaha Jasa Pasokan dan Pemeliharaan Ban Alat Berat di PT Bukit Jaya Utama - Bukit1, Matius Tomaja; Syarief, Rizal; Kadarisman, Darwin (Institut Pertanian Bogor, 2021)
The increasingly intense competition in the business world at this time has made business actors must have